The Effects of Climate Change: Another Reason to Rethink Migration Policies - Gutiérrez López, Eduardo Elías (2022)
There are many global challenges ahead, however, within the discussions on public policy and legislation, little is addressed about migration as a result of the impacts of climate change. The study of the relationship between migration and climate change is intricate in comparison to the analyses that emphasize other causes of human mobility, but the projected global scenario calls for more attention to this factor. This global panorama requires action by national Governments, as well as rethinking the political rationality with which migration is currently regulated and managed. Therefore, this work aims to carry out a theoretical analysis of the main political positions on the migratory phenomenon that countries have assumed and to discuss to what extent they are relevant to the future demands on climate change. The methodology used is analytical and is based on breaking down the main migration policies in all their parts and types and contrasting them with the laws and actions implemented by countries and international communities. All this to establish that the main political rationales with which the migration issue is regulated and managed are insufficient to address the consequences of a global and inevitable phenomenon such as climate change.